Issues On the Modern Technologies in Teaching Foreign Languages - Artikova Makhim Turaboy kizi (Genius Journals, 2022)
The article deals with the issues based on application of modern technologies in teaching FL and considers the educational possibilities of modern information technologies, as well as the design and creation of an electronic training course aimed at studying foreign languages. Awareness of the fundamental role of information in social development and the huge growth rates of information technologies have necessitated the formation of a special information culture of the individual. For today's student, who will live in the information society of the future, the computer should become an integral part of his life. Therefore, the use of information and communication technologies (ICT) in the educational process is an urgent problem of modern education.
Keywords: Foreign Languages; Modern; urgent; Information